Americium and Plutonium Purification by Extraction (the AMPPEX process): Development of a new method to separate 241Am from aged plutonium dioxide for use in space power systems. (July 2018) - Brown, Jamie; Campbell, Catherine; Carrigan, Cheryl; Carrott, Michael; Greenough, Katie; Maher, Chris; McLuckie, Bliss; Mason, Chris; Gregson, Colin; Griffiths, Tamara; Holt, Josh; Sarsfield, Mark; et al.
Abstract: One of the most successful uses of nuclear energy, other than nuclear fission reactors, is the use of radioisotopes to provide a simple source for heat and electrical power in space applications. The alpha decay heat from suitable radioisotopes can be harnessed to heat instrumentation and generate electricity through thermoelectric generators. Within Europe, the feasibility of using americium ( 241 Am) in such applications is being considered. Part of this study is to develop a way to access a stock of suitable material and the UK stockpile of separated civil plutonium dioxide, generated through reprocessing operations, is a rich source of americium. This paper summarises 5 years of development work performed to establish a way to separate americium from the plutonium dioxide in a safe and cost effective way, generating a high purity product with high recovery efficiency. Graphical abstract: Image 1 Highlights: 5 years of development work is described for 241 Am production from a plutonium dioxide feedstock. 241 Am and plutonium products are produced in high yield (>99%) and high purity (>99%). A solvent system is defined and optimised to give the best americium recovery and minimise radioactive wastes. Americium oxalate precipitation and thermal decomposition is used to recover the americium as an oxide.